CERAMIC ART MADE IN TURKEY ON THE GRADUATE THESIS TO CIRCULAR EVALUATIONS (1987-2020) - Yasemin GÜL (Fırat University, 2021)
As it is known, the history of ceramic art goes back to old times. Anatolian lands hosted many civilizations and communities. As a natural consequence of this, ceramic art has been affected by this accumulation while continuing its development. This art, which continued its existence in the form of pottery for long periods, has been transformed into a form of Contemporary Ceramic Art since the last period of the Ottoman Empire and the first years of the Republic, by being influenced by Europe. The opening of European schools in the early years of the republic contributed to the development of important ceramic artists who will lead this art and as a result of the rapid development of ceramic art. Especially since the early 1980’s opening ceramic departments within vocational schools and faculties is an important step for associate and undergraduate education at universities. Later, it is known that graduate and arts proficiency training is done in the programs opened within the Social Sciences and Fine Arts Institutes of universities. In this study, graduate theses made on the basis of ceramic art in Turkey, has made a number of conclusions. In the introduction part, the history of the art of ceramics, the first years of the Republic and the situation after 1980 are mentioned in general terms. In the second part, postgraduate theses in the field of ceramic art registered in the Higher Education Institution National Thesis Center were determined and examined. Distribution of graduate theses by years and universities has been revealed. Thesis studies on ceramic art have been evaluated by using tables and graphics. In the conclusion part, a number of inferences mentioned in the text are presented in general terms. In the Annexes, graduate theses are turned into tables.